Cruciate ligament, patellar tendon, and patella formation involves differential cellular sources and dynamics as joint cavitation proceeds. Issue 6 (10th February 2020) - Zhang, Yi; Kameneva, Polina; Annusver, Karl; Kasper, Maria; Chagin, Andrei S.; Adameyko, Igor; Xie, Meng
Abstract: Background: Cruciate ligament (CL) and patellar tendon (PT) are important elements of the knee joint, uniting femur, patella, and tibia into a single functional unit. So far, knowledge on the developmental mechanism of CL, PT, and patella falls far behind other skeletal tissues. Results: Here, employing various lineage tracing strategies we investigate the cellular sources and dynamics that drive CL, PT, and patella formation during mouse embryonic development. We show that Gdf5 and Gli1 are generally expressed in the same cell population that only contributes to CL, but not PT or patella development. In addition, Col2 is expressed in two independent cell populations before and after joint cavitation, where the former contributes to the CL and the dorsal part of the PT and the latter contributes to the patella. Moreover, Prrx1 is always expressed in CL and PT progenitors, but not patella progenitors where it is switched off after joint cavitation. Finally, we reveal that patella development employs different cellular dynamics before and after joint cavitation. Conclusions: Our findings delineate the expression changes of several skeletogenesis‐related genes before and after joint cavitation, and provide an indication on the cellular dynamics underlying ligament, tendon, and sesamoid bone formation during embryogenesis. Key Findings: Cellular dynamics underlying ligament, tendon and sesamoid bone formation during embryogenesis.